Morocco - Oum Er Rbia Irrigated Agricultural Modernization Project : Helping Farmers Increase Productivity - Bucknall, Julia; Lamrani, Hassan (World Bank, Washington, DC, 2012)
This operation provides a $70m loan for a project that would help participating farmers in the Oum Er Rbia basin increase the productivity of their farming and to promote more sustainable use of irrigation water to overcome current and future water deficits. This would be achieved by providing participating farmers with the level of irrigation service necessary for high efficiency drip irrigation. Scarcity and degradation of water resources have reached alarming levels in Morocco. In addition, water resources are unevenly distributed throughout the country and rainfall is highly variable. Droughts are common. Ninety percent of economically accessible surface resources are already controlled by dams, leaving few options for additional surface water storage. Population and economic growth have increased demand even as supply has fallen. The problems are particularly acute in the Oum Er Rbia basin. However, on average over the past decade, the basin's Large Scale Irrigation (LSI) schemes received only 60 percent of the water for which the system was designed. Government of Morocco has been pursuing reforms to improve water management and service delivery. The water allocation system is the responsibility of the River Basin Agencies, which were created to promote integrated and participatory water resource management. This note is based on the Project Appraisal Document (PAD). The project was declared effective only in September 2010 so it is too early for any implementation lessons to be collected.